Peran Strategi Manajemen Talenta dalam Peningkatan Kinerja Karyawan – Suatu Telaah Sistematik Literatur - Dedi Setiawan Dedi Setiawan; Nurmala Nurmala (Vokasi: Jurnal Publikasi Ilmiah, 2025)
Abstract  This article aims to explore the role of talent management strategies in improving employee performance. This study uses a systematic literature review (SLR) approach to explore the concept of talent management strategy and employee engagement in the context of human resource science. Thematic analysis was conducted to synthesize the findings of the publications reviewed regarding talent management strategies and their implementation related to employee engagement. Talent model can be built with two main variables, namely talent management mindset and talent management strategy. Both of these variables can affect talent management practices. Talent management strategy and generational group preferences have a strong correlation. Meanwhile, the organizational environment that influences the adoption and integration of a healthy talent management strategy. Important factors in the integration of talent management strategy is the formation of a healthy talent-wellness organizational culture. The concept of talent management strategy and employee has been studied in human resource management research and practice. This study offers new insight and management practice from the concept of talent management strategy in the psychological interaction of employees in the work environment.